KAJIAN SIMULASI PENGARUH TEKANAN BALIK GAS BUANG TERHADAP KINERJA MESIN SEPEDA MOTOR EMPAT LANGKAH 135CC - Sefnath Sarwuna; Wegie Ruslan; Indra Setiawan (Magister Teknik Mesin Universitas Pancasila, 2017)
It is generally known that exhaust system or commonly called muffler is a vital/main part of amotor cycle. Therefore in the automotive sector/field, this product is progressing rapidly andincreasing the customer. Exhaust functions are to increase to speed, to beautify the shape and toacquire the good sound hearing. But infect, many people disregard to improve/increase engineperformance by utilizing the exhaust gas itself. Related to exhaust gas issue and focus on backpressure that occurs during disposal process, some exhaust products with different size of headerdiameter are taken and analyzed to determine the amount of back pressure generated. Theanalysis using ANSYS R15.0 program and the direct test using DYNOJET Model 250.Thesimulation result show the amount of back pressure that occurs in the header exhaust for each typeof exhaust. The first type of exhaust (muffler type 1) the largest/the most back pressure is 3172.04Pa, for the second type of exhaust (muffler type 2) the pressure is 2775.66 Pa, the third type ofexhaust (muffler type 3) produce 1138.39 Pa back pressure and the fourth type of exhaust (mufflertype 4) produce the smallest back pressure is 562.64Pa.The result of the four stroke 135cc motorcycle for each type of muffler using the Dynojet show that the muffler type 1 on the 7340 rpm maxtorque 0.89 kg.m (8.73 N.m) on round of 8150 rpm generating a max power 9.26 PS (6811 watt).For muffler type 2 on around 7160 rpm produce max torque 1.05 kg.m (10.3 N.m) and max power10.57 PS (7774.21 watt). For muffler type 3 at the around 7250 rpm produce max torque 1.13kg.m (11.08 N.m) and max power 11.50 PS (8458.22 watt). And for muffler type 4 at around 7240rpm produce max torque 0.95 kg.m (9.31 N.m) and at the around 8520 rpm obtained the maxpower is 10.26 PS (7546.21 watt). Torque and the biggest power generated by the muffler type 3while torque and smallest power generated by the muffler type 1.